The Challenges Of Boko Haram Insurgency: Implications For Nigeria’S National Security, 2009-2017 - Mustapha, Mohammed (2022)
This research examines challenges of Boko Haram insurgency and implications for Nigeria’s national security, with the scope covering the period from 2009 until 2017. The scope is purposely chosen to start from when the BH terrorist group became more violent. This period witnessed consistent and ruthless attacks by the BH terror group in northeastern Nigeria, with devastating consequences on the national security architecture of Nigeria. The theoretical basis of this study lays emphasis on Emile Durkheim and Robert K. Merton's Anomie Theory. Qualitative methods of research inquiry were used to generate data and Content Analysis as methodology. The data were collected using the key informant interview (KII) and focus group discussion (FGD). A total of 210 respondents participated in this study, 30 in-depth interviews for the KII, and 18 group discussions of 10 participants in each cluster of both Adamawa and Borno states. The participants are selected using the purposive and criterion sampling techniques of those who played active roles in the fight against Boko Haram insurgency and those directly affected by Boko Haram terrorism. Data collected were analysed using content analysis and coding.